Challenges in Authenticity Check of Student Papers at the Study of Digital Economy - Sokele, Mladen; Kuvacic, Dalija; Moric, Sanja (2024 47th MIPRO ICT and Electronics Convention (MIPRO), 2024)
The accelerated development of information technology and artificial intelligence tools that assist students in written assignments have become an increasing challenge for teachers in verifying their authenticity. The goal of this research is to determine the differences of seminar papers and master theses at the Professional Graduate Study of Digital Economy, before and after the possibility of artificial intelligence aid usage. The comparison is carried out by analyzing detailed reports from the Turnitin originality checking service as well as complementary indicators for effective number of different sources and similarity index per source based on the Herfindahl-Hirschman index. In addition, a quantitative linguistic analysis of sample sets of master's theses was performed and it was shown that such analysis can be useful for detecting text generated by artificial intelligence. To maintain the quality of study and preserve the alignment of student competencies with the qualification they acquire upon completion of the educational program, there is an equal importance of systematic monitoring of students' progress, academic integrity awareness empowerment and adequate forms of knowledge assessment.